Advanced Adaptive Photonic RF Filters with 80 Taps Based on an Integrated Optical Micro-Comb Source - Xu, Xingyuan; Tan, Mengxi; Wu, Jiayang; Nguyen, Thach G.; Chu, Sai Tak; Little, Brent E.; Morandotti, Roberto; Mitchell, Arnan; Moss, David J. (Journal of lightwave technology, 2019)
We demonstrate a photonic radio frequency (RF) transversal filter based on an integrated optical micro-comb source featuring a record low free spectral range of 49 GHz, yielding 80 micro-comb lines across the C -band. This record high number of taps, or wavelengths for the transversal filter results in significantly increased performance including a Q RF factor more than four times higher than previous results. Furthermore, by employing both positive and negative taps, an improved out-of-band rejection of up to 48.9 dB is demonstrated using a Gaussian apodization, together with a tunable center frequency covering the RF spectra range, with a widely tunable 3-dB bandwidth and versatile dynamically adjustable filter shapes. Our experimental results match well with theory, showing that our transversal filter is a competitive solution to implement advanced adaptive RF filters with broad operational bandwidth, high frequency selectivity, high reconfigurability, and potentially reduced cost and footprint. This approach is promising for applications in modern radar and communications systems.